Optimism, mindfulness, and resilience as potential protective factors for the mental health consequences of fear of the coronavirus - Vos, Lisa M.W.; Habibović, Mirela; Nyklíček, Ivan; Smeets, Tom; Mertens, Gaëtan (Psychiatry research, 2021)
•Fear of COVID-19 is related to increased depression, anxiety, and stress.•We investigated whether this relationship is moderated by positive traits.•Mindfulness, optimism, and resilience were included in this study (N = 546).•We found evidence for a moderating effect of these positive traits.•The results suggest that positive traits protect against distress due to COVID-19. The COVID-19 pandemic has a substantial impact on mental health. Prior reports have shown that depression, anxiety, and stress have increased throughout the pandemic. Nonetheless, not everyone is affected by these negative consequences and some people may be relatively unaffected. In this online study in a predominantly Dutch and Belgian sample (N = 546), we investigated whether positive personality traits such as optimism, mindfulness, and resilience may protect against the negative mental health consequences (i.e., fear of the coronavirus, depression, stress, and anxiety) of the COVID-19 pandemic. We found that fear of COVID-19 was related to higher depression, stress, and anxiety. However, for participants scoring high on mindfulness, optimism, and resilience, this relationship was weakened. In addition to these findings, we present the results of network analyses to explore the network structure between these constructs. These results help to identify possible ways through which psychological well-being can be promoted during the COVID-19 pandemic.